Gênero textual digital meme: um estudo sobre ensino de língua portuguesa e letramentos - Flávio Martins da Silva (2021)
The Base Nacional Comum Curricular (Brazilian Common Core) institutionalized and expanded the use of digital textual genres, including the meme, in Portuguese language teaching in Brazil’s basic education system. This study aims to understand and discuss the use of the textual genre meme in the final years of elementary school and its potential uses, from the perspective of teachers, for the development of reading and writing enhanced by critical thinking. This study is based upon qualitative methodological approach and the field for data collection took place in a mini-course offered to 35 teachers participating in the research and were collected through video recordings; observation and field notes and questionnaires applied before and after the mini-course. Data analysis showed that most of the teachers had superficial ideas about the GTD meme and that although they presented some level of difficulty in inserting this type of genre in their classes, they recognized the importance of updating the list of resources for the teaching of Portuguese language. This research contributes to the studies of the digital textual genre, as it presents situations of applied use of GTD that enhance reflections on digital and critical literacy from the use of memes.